Digital next-generation sequencing identifies low-abundance mutations in pancreatic juice samples collected from the duodenum of patients with pancreatic cancer and intraductal papillary mucinous neoplasms. Issue 9 (18th July 2016) - Yu, Jun; Sadakari, Yoshihiko; Shindo, Koji; Suenaga, Masaya; Brant, Aaron; Almario, Jose Alejandro Navarro; Borges, Michael; Barkley, Thomas; Fesharakizadeh, Shahriar; Ford, Madeline; Hruban, Ralph H; Shin, Eun Ji; et al.
Abstract : Objective: Secretin-stimulated pancreatic juice contains DNA shed from cells lining the pancreatic ducts. Genetic analysis of this fluid may form a test to detect pancreatic ductal neoplasia. Design: We employed digital next-generation sequencing ('digital NGS') to detect low-abundance mutations in secretin-stimulated juice samples collected from the duodenum of subjects enrolled in Cancer of the Pancreas Screening studies at Johns Hopkins Hospital. For each juice sample, digital NGS necessitated 96 NGS reactions sequencing nine genes. The study population included 115 subjects (53 discovery, 62 validation) (1) with pancreatic ductal adenocarcinoma (PDAC), (2) intraductal papillary mucinous neoplasm (IPMN), (3) controls with non-suspicious pancreata. Results: Cases with PDAC and IPMN were more likely to have mutant DNA detected in pancreatic juice than controls (both p<0.0001); mutant DNA concentrations were higher in patients with PDAC than IPMN (p=0.003) or controls (p<0.001). TP53 and/or SMAD4 mutations were commonly detected in juice samples from patients with PDAC and were not detected in controls (p<0.0001); mutant TP53 / SMAD4 concentrations could distinguish PDAC from IPMN cases with 32.4% sensitivity, 100% specificity (area under the curve, AUC 0.73, p=0.0002) and controls (AUC 0.82, p<0.0001). Two of four patients who developed pancreatic cancer despite close surveillance had SMAD4/TP53 mutations from their cancer detected in juice samples collected over 1 year prior to their pancreatic cancer diagnosis when no suspicious pancreatic lesions were detected by imaging. Conclusions: The detection in pancreatic juice of mutations important for the progression of low-grade dysplasia to high-grade dysplasia and invasive pancreatic cancer may improve the management of patients undergoing pancreatic screening and surveillance.